2009
DOI: 10.1007/s00431-009-0982-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice

Abstract: Sleep problems are very prevalent during infancy. The most common problems are those related to night wakings and sleep-disordered breathing (SDB). Most common night waking problems do not have identified physiologic etiology. Their causes appear to be behavioral or developmental by nature, and they usually respond well to behavioral interventions. SDB may result from a variety of anatomic and neurologic factors and is associated with a variety of medical and developmental disorders. Because of the high preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The prevalence of sleep problems in children in the general population is up to 30% [2,3]. Gender and age influence sleep [3-5], and some sleep problems are more common during certain stages of child development, such as night wakings during infancy [6] and sleep onset delay in older children [3]. Children with sleep difficulties experience higher rates of behavioral problems, depression, anxiety in adulthood, and impaired cognitive function and emotional development [6-11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of sleep problems in children in the general population is up to 30% [2,3]. Gender and age influence sleep [3-5], and some sleep problems are more common during certain stages of child development, such as night wakings during infancy [6] and sleep onset delay in older children [3]. Children with sleep difficulties experience higher rates of behavioral problems, depression, anxiety in adulthood, and impaired cognitive function and emotional development [6-11].…”
Section: Introductionmentioning
confidence: 99%
“…Gender and age influence sleep [3-5], and some sleep problems are more common during certain stages of child development, such as night wakings during infancy [6] and sleep onset delay in older children [3]. Children with sleep difficulties experience higher rates of behavioral problems, depression, anxiety in adulthood, and impaired cognitive function and emotional development [6-11]. Sleep problems are more common in certain medical conditions, such as chronic pain, attention deficit hyperactivity disorder, and autism [12-14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a prevalence of sleep disorders in children up to 30% [2, 3, 17]. Some sleep problems are more common during certain stages of child development, such as night wakings during infancy [28], Children with sleep difficulties experience higher rates of behavioral problems, depression, anxiety in adulthood, impaired cognitive function, learning disabilities, and emotional development [1, 7, 9, 10, 15, 27]. Sleep problems are more common in certain medical conditions, such as chronic pain, attention deficit hyperactivity disorder (ADHD), and autism [16, 19, 22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, around 60–70% of four-month olds meet the criterion of sleeping continuously for periods of 5 h or more most nights per week (Moore and Ucko, 1957; St James-Roberts et al ., 2001; Henderson et al ., 2010). However, around a third of infants in many countries sleep for short periods and ‘signal’ (cry out) on waking in the night, making this the most common type of infant sleep behaviour problem (Sadeh and Sivan, 2009; Mindell et al ., 2010). Most such infants are healthy (Mindell, 2008; Sadeh and Sivan, 2009), but their night-time behaviour can exhaust or depress parents and generate substantial health service costs (Morris et al ., 2001; Dennis and Ross, 2005; Stremler et al ., 2013).…”
mentioning
confidence: 99%
“…However, around a third of infants in many countries sleep for short periods and ‘signal’ (cry out) on waking in the night, making this the most common type of infant sleep behaviour problem (Sadeh and Sivan, 2009; Mindell et al ., 2010). Most such infants are healthy (Mindell, 2008; Sadeh and Sivan, 2009), but their night-time behaviour can exhaust or depress parents and generate substantial health service costs (Morris et al ., 2001; Dennis and Ross, 2005; Stremler et al ., 2013). Preventive interventions have the potential to help families and improve service cost-effectiveness.…”
mentioning
confidence: 99%